Analisis kepercayaan diri mahasiswa pendidikan matematika dalam pembelajaran daring di era pandemi covid-19 - Fitriani Fitriani; Benny Sofyan Samosir; Winmery Lasma Habeahan (Mahesa Research Center, 2021)
Self-confidence is one of the affective aspects that must be considered and developed, especially in building student readiness in undergoing online learning in the current pandemic era. This study aims to analyze the confidence of mathematics education students in online learning in the era of the covid-19 pandemic. This research use descriptive qualitative approach. The subjects of this study were first semester students who took the Differential Calculus course in the Mathematics Education study program at the Universitas Muhammadiyah Tapanuli Selatan for the 2021/2022 academic year. The instrument used in this research is a questionnaire. The data obtained in this study were analyzed descriptively. Based on the results of the study, it shows that the indicators of student self-confidence in online learning in the era of the covid-19 pandemic have not fully achieved, but most of the indicators have mostly achieved self-confidence, namely the first indicator of believing in self-ability, most of them have achieved self-confidence. Students also have not fully met the second indicator, namely being able to act independently in making decisions. In the third indicator having a positive self-concept, most students have achieved this indicator. In the fourth indicator, namely daring to express opinions, almost some students have the courage to express opinions. To further increase student confidence, it is necessary to provide innovation in the implementation of online learning.